Determining Dimensions of Job Satisfaction among Employees: Evidence from Commercial Bank Industries in Bangladesh - Md. Sayed Uddin; Md. Atikur Rahaman; Wasib Bin LATIF (ResearchGate, 2023)
Since the banking industry relies so heavily on strong customer-staff interactions, measuring employee job satisfaction has become a critical problem. To achieve benefits for both individuals and organizations, it is crucial to foster and ensure employee job satisfaction. The main objective of this study is to determine the influencing factors of employees’ job satisfaction in commercial banks in Bangladesh. This study focused on some significant factors such as employee empowerment, job security, management support, and attractive compensation in an organization. In terms of research purpose, non-probability convenience sampling has been used, and the study is quantitative in nature. For data collection purposes, an online survey questionnaire was prepared based on previously published articles. The targeted population was the bank employees of commercial banks in Bangladesh where the final sample size was n = 200. For analyzing the collected data, SPSS 26.0 version has been used to test the study model and the proposed hypotheses. This study also shows that employee empowerment, job security, management support, and attractive compensation have positive and significant effects on employees’ job satisfaction at the workplace. Finally, this study has offered some extraordinary directions and implications for future research on commercial bank authorities in Bangladesh.